Validating Children 's Stories and Decisions after Trafficking for Prostitution - Ifeyinwa Mbakogu (CV. Literasi Indonesia, 2020)
Research on trafficking for prostitution in West Africa is focussed mostly on the experiences of women. When attention is directed to children, their voices are silent; and attention is placed on traffickers, therefore, downplaying the role of relatives in children’s movement from home. Moreover, when children are removed from trafficking, the usual path to re-integration is to unite them with their parents. Two issues drive this paper: if a parent that is implicated in the trafficking of their child for prostitution should be included in decision-making for reintegrating the child; and if a child understands their experience of trafficking to make informed decisions about moving on after trafficking. Based on this foundation, the paper explores one child’s journey from Nigeria to Burkina Faso for prostitution, with attention to the child’s perspectives on their journey and decisions for moving on after trafficking to inform the inclusion of children trafficked for prostitution in decisions about their reintegration.